ANALYSIS OF ECONOMIC CONDITION IN THE GEORGER WARKER BUSH. ERA AS REFLECTED IN THE NOVEL THE HUSBAND BY DEAN KOONTZ - Citra Yunus Giawa; Risnawaty Risnawaty; Milisi Sembiring (Fakultas Sastra UMN AL Washliyah, 2023)
The analysis of this research is the novel